Influenza Viruses: Innate Immunity and mRNA Vaccines - Lee, SangJoon; Ryu, Jin-Hyeob (Frontiers in Immunology, 2021)
The innate immune system acts as the first line of defense against influenza virus. Influenza virus causes severe inflammation in the respiratory tract and leads to more than 650,000 annual deaths worldwide. mRNA vaccines represent a promising alternative to conventional vaccine approaches because of their safe administration, low-cost manufacture, capacity for rapid development, and high potency. In this review, we focus on our current understanding of the innate immune response that uses pattern recognition receptors to detect and respond to the mRNA vaccination. We also provide an overview of mRNA vaccines and consider future directions and challenges in advancing this promising vaccine platform to use as a therapeutic approach.